2020
DOI: 10.4103/aja.aja_97_19
|View full text |Cite
|
Sign up to set email alerts
|

Y chromosome microdeletion screening using a new molecular diagnostic method in 1030 Japanese males with infertility

Abstract: The azoospermia factor (AZF) region is important for spermatogenesis, and deletions within these regions are a common cause of oligozoospermia and azoospermia. Although several studies have reported this cause, the present research, to the best of our knowledge, is the first large-scale study assessing this factor in Japan. In this study, 1030 male patients with infertility who were examined for Y chromosome microdeletion using the polymerase chain reaction-reverse sequence-specific oligonucleotide (PCR-rSSO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Deletions in the AZFc region do not always cause azoospermia, and gr / gr deletions are commonly observed in a certain percentage of Asian people. Iijima et al reported that the frequency of AZF microdeletions in Japanese men was similar to that reported in patients from other countries, and the sperm retrieval rate was higher in patients with AZFc deletions 18 …”
Section: Azf Microdeletion and Congenital Bilateral Absence Of The Vas Deferenssupporting
confidence: 61%
“…Deletions in the AZFc region do not always cause azoospermia, and gr / gr deletions are commonly observed in a certain percentage of Asian people. Iijima et al reported that the frequency of AZF microdeletions in Japanese men was similar to that reported in patients from other countries, and the sperm retrieval rate was higher in patients with AZFc deletions 18 …”
Section: Azf Microdeletion and Congenital Bilateral Absence Of The Vas Deferenssupporting
confidence: 61%
“…This indicated that gr/gr deletions do not influence spermatogenesis in the Japanese population 77 . In 2019, Iijima et al, 78 the same research group, reported almost the same proportion of gr/gr deletions among 1030 infertile males in Japan. However, they also stated that SRR in patients with gr/gr deletion was relatively lower than that in patients without the deletion (18.8% vs 28.7%, P = .09), although the difference was not statistically significant.…”
Section: Testing For Genetic Abnormality In Clinical Practicementioning
confidence: 93%
“…Prior to the present study, all patients underwent conventional G‐banding analysis for 20 peripheral leukocytes and were found to have a normal 46,XY karyotype. In addition, the patients were subjected to copy‐number analysis of the AZF regions, which showed the lack of AZF deletion in 132 of 198 patients. The common gr/gr, AZFb, AZFc, and AZFb+c deletions were detected in 49, 1, 15, and 1 patient(s), respectively.…”
Section: Methodsmentioning
confidence: 99%